THE EFFECT OF USING INSTRUCTIONAL VIDEO MEDIA ON THE LEARNING OUTCOMES OF GRADE IV STUDENT IN SOCIAL SCIENCE SUBJECTS AT SD NEGERI 91 SOREANG DESA TAMALATE KECAMATAN GALESONG UTARA - Anita Purnama Hani (International Journal of Elementary School Teacher, 2022)
This study is an experimental study that aims to see whether there is an effect of using video media on student learning outcomes in social studies subjects for class IV SD Negeri 91 Soreang. The research design used is the None Equivalent Control Design. The independent variable of this research is video media. The dependent variable is learning outcomes. The study population was 36 students with 21 males and 15 females consisting of two classes. The sampling technique used is purpose sampling. The instrument that the researcher uses is in the form of multiple choice questions, totaling 20 questions. Data collection techniques are tests, observations and documentation. The data analysis technique used descriptive statistics and inferential statistics using independent sample T-test. The results of the hypothesis test showed that video media had an effect on learning outcomes. The application of video media in the fourth grade of SD Negeri 91 Soreang is in the very good category. Student learning outcomes in social studies subjects in the control and experimental classes were in the good category. The conclusion of this study is that video media has an effect on social studies learning outcomes for fourth grade students of SD Negeri 91 Soreang.